(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the world’s first and foremost for his blessings, and may God’s prayers be upon our Master and Prophet Muhammad (may God’s prayers and peace be upon him and his family) and upon the God of the pious, the pure, the sick, the noble. Education occupies a supreme place in the heritage of the Ahl al-Bayt (peace be upon them), and research on education is not a new topic, but the current situation needs to draw boundaries commensurate with the development of ideas and refer through them to a pure name, and this research deals with something of that, as Islamic education The thought of the people of the house (peace be upon them) is of a great and honorable status, as the researcher divided the research into an introduction, two papers and a conclusion. The first topic dealt with the vocabulary of the research tagged: (Islamic education in the thought of the people of the house (peace be upon them)) and the second topic dealt with demands on the teacher, the learner and the curriculum, and it was The conclusion included a statement of a very important matter, which is not to refer to the heritage and read it in a reading commensurate with the requirements of the times, and we see the decline, delusion, and dimension in all aspects of life, Islam came to save humanity, and God is behind the intent, and he is considered to be us and yes, the agent.